Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2019)
A new omaliine genus and species from northern Vietnam, Prosoglypta alesenkae Shavrin & Smetana gen. et sp. nov., is described and illustrated. The main morphological features of the new genus and its taxonomic relations with other genera of the tribe Omaliini MacLeay, 1825 are briefly discussed.